Constitutionalisation of private law - Barkhuysen, T. (Tom), 1968-; Lindenbergh, S. D. (Siewert Doewe), 1964- (Constitutional law library, 2006)
Aims at establishing an analysis of the nature and growth of the C-factor (C for constitutionalisation) in Germany, France, the UK and The Netherlands. This analysis will be followed by answering the questions: how are these developments to be judged? Does the C-factor seriously undermine the autonomy of private law?